Evaluation and Planning of Required of Base Transceiver Station (BTS) in Nunukan Regency - Pusvita, Vita (Jurnal Pekommas, 2018)
Nunukan Regency has geographical conditions that can prevent directly public services. Implementation of online public service can help government to reach community. However, the lack of telecommunication access, especially inaccessibility of users or  the lack  of  BT capacity , is a major obstacle in the implementation of these service. Therefore, evaluation and planning of BTS requirement is needed in order to reach all users. The purpose of this research is to evaluate and  plan  the requirement of telecommunication tower in Nunukan Regency. This study used two methods in determining the BTS requirement by using the Standford University Interim (SUI) propagation model to determine the coverage area of telecommunication towers and using the calculation of BTS capacity to meet traffic requirements. The result obtained is  the number of base stations which recorded  are able to meet traffic requirements if it is assumed that all base stations which have been built are macro BTS with 3 sector antenna specification and the number of carriers 1 or 2, or micro BTS with 3 sectors antenna specification and  the number of carriers 2. However, if it does not meet these specifications, it is necessary to increase the number of BTS based on BTS capacity for all sub-districts, except Krayan, Kraya Timur,  Krayan Tengah and Krayan Barat.